Effects of different feedback types on information integration in repeated monetary gambles - Haffke, Peter; Hübner, Ronald (Frontiers in Psychology, 2015)
Most models of risky decision making assume that all relevant information is taken into account (e.g., Kahneman & Tversky, 1979; von Neumann & Morgenstern, 1944). However, there are also some models supposing that only part of the information is considered (e.g., Brandstätter, Gigerenzer, & Hertwig, 2006; Gigerenzer & Gaissmaier, 2011). To further investigate the amount of information that is usually used for decision making, and how the use depends on feedback, we conducted a series of three experiments in which participants choose between two lotteries and where no feedback, outcome feedback, and error feedback was provided, respectively. The result show that without feedback participants mostly chose the lottery with the higher winning probability, and largely ignored the potential gains. The same result occurred when the outcome of each decision was fed back. Only after presenting error feedback (i.e., signaling whether a choice was optimal or not), participants considered probabilities as well as gains, resulting in more optimal choices. We propose that outcome feedback was ineffective, because of its probabilistic and ambiguous nature. Participants improve information integration only if provided with a consistent and deterministic signal such as error feedback.